Hábitos alimentarios y estado nutricional de los escolares de la Parroquia San Pedro de la Bendita - Elizalde Merino, Evelyn Katherine (2023)
Nutritional status is a useful indicator of individual and population health and well-being, influenced by eating habits, when these are of poor quality, their consequences are inhibition of cognitive development and increased infant morbidity and mortality. For this reason, the present relational, quantitative, cross-sectional and prospective research was proposed to identify the nutritional status, establish eating habits, and to know the relationship of the variables, in 164 schoolchildren from the parish of San Pedro de la Bendita. The information was obtained through a data collection sheet, which included three sections: the first aimed at collecting demographic data; in the second, the growth graphs of the WHO 2007 were recorded, with which nutritional status was obtained; and, the Krece-Plus test to know the eating habits, finding that 44% (n=72) showed normality in the nutritional state, with predominance in the masculine sex. Regarding age, 54% (n=89) of Children from 9 to 11 years old obtained average quality in eating habits. Finally, with the Chi squared test was established, there is a relationship between eating habits and nutritional state. Schoolchildren with poor quality eating habits suffer from malnutrition, particularly by excess